Intellectual property law: In the hands of artificial creator - N. V. Kozlova (Цифровое право, 2021)
Review of a book:  Lee, J-.A., Hilty, R., & Liu, K-.C. (Eds.). (2021). Artiﬁcial intelligence and intellectual property. Oxford University Press. https://doi.org/10.1093/oso/9780198870944.001.0001